Liberdade, igualdade e participação como garantia da democracia direta em Jean-Jacques Rousseau - Rossetto, Maicon Rodrigo (Universidade do Vale do Rio dos Sinos, 2016)
The research takes as a central study object the understanding of direct democracy in Jean-Jacques Rousseau. It presents that the political principles of liberty, equality and participation are the warranty basis of direct democracy according to the genevois thinker. It refutes the opposite positions of Bertrand Russell, Jacob Talmon and Isaiah Berlin, which accuse the rousseaunian conception of containing totalitarian political positionings. The research shows that these critic’s interpretations are biased, and thus, mistaken. The defense of Rousseau’s direct democracy against its accusations of totalitarianism takes into account several aspects of his thinking: the hypothesis of the state of nature, which identifies in the natural man the characteristics of natural freedom, natural equality, independence and gifted with self-love; and the characteristics identified in the civil man/citizen that are presented in the work The Social Contract, as civil liberty, civil equality and participation. The direct democracy has in liberty, in equality and in participation principles that guarantee the possibility of thinking one political system in that the citizen may follow the laws he gives to himself, and not to a will outside of his own; in that inequality does not constitute dependence of some over others; and that participation is an effective exercise of the citizen as a subject of the political process, thus deconstructing every sort of passivity and political dependence. This way the thesis that Rousseau could be identified as totalitarian lies secluded, and conversely it is shown that his conception for direct democracy is effectively affirming of freedom, equality and participation.
Keywords: Rousseau; Democracia; Liberdade; Igualdade; Participação; Totalitarismo; Democracy; Liberty; Equality; Participation; Totalitarianism; ACCNPQ::Ciências Humanas::Filosofia